Grand stand built for Fourth of July celebration on Front Street in front of the Yukon Dock Company building, Dawson, Yukon Territory, 1901. - Cantwell, George G.
Caption on image: "Grand stand. Dawson July 4th 1901" PH Coll 246.51 [Meed journal: "Grand stand on shore side of Front Street against the Yukon Dock. July 1901. Occasion - the athletic sports in celebration of American 4th of July holiday."] To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number